Remarkable population structure in the tropical Atlantic lace corals Stylaster roseus (Pallas, 1766) and Stylaster blatteus (Boschma, 1961) - Mariana Gnecco; Flávia L. D. Nunes; Fanny L. González-Zapata; Luisa F. Dueñas; Carla Zilberberg; Alberto Lindner; Juan A. Sánchez (Coral Reefs, 2023)
Biodiversity on coral reefs depends not only on primary reef-builders, but also on associated taxa that create microhabitats for other species. Hydrocorals of the genus Stylaster , commonly known as lace corals, form small branching colonies that enhance three-dimensional complexity on reefs and are known to support a variety of commensal species. Furthermore, the genus is highly speciose, further increasing biodiversity. Despite their important ecological roles, little is known about the evolutionary history and the intraspecific diversity and structure in these broadly distributed hydrocorals. Here, we assessed the phylogenetic relationships among Atlantic species in the genus Stylaster and examined the genetic structure of S. roseus in the Tropical Western Atlantic (Caribbean and Brazil) and of S. blatteus in the Tropical Eastern Atlantic (Africa), using DNA sequences from the 16S ribosomal gene. Time-calibrated phylogenetic analyses showed that S. roseus and S. blatteus diverged at ~ 24.6 Ma. A well-supported Brazilian clade within S. roseus indicates a possible cryptic species that diverged at ~ 11.6 Ma, consistent with the formation of the Amazon River at 9 Ma (Hoorn et al. in Glob Planet Change 153:51–65, 2017). Strong genetic structure was observed even over moderate distances, with Φ ST values over all populations being 0.98 for S. roseus and 0.90 for S. blatteus . Nearly, all haplotypes were private (found in a single location) and diverged by many mutational steps from one another. In contrast, genetic diversity was low at the local scale for both species, with most sites showing no variation (a single haplotype). These results are coherent with the reproductive strategy of Stylasteridae, where larvae are brooded and are highly developed at the time of release, often settling near the parental colony. Limited dispersal coupled with possible clonal reproduction have likely contributed to the high levels of genetic differentiation observed here. Lace corals show unusual reproductive and population dynamics compared to other reef inhabiting cnidarians. Future work may reveal additional cryptic diversity in this poorly studied family.

Brazilian marine biogeography: a multi-taxa approach for outlining sectorization - Isadora Cord; Lucas T. Nunes; Cristiane X. Barroso; Andrea S. Freire; Otto B. F. Gadig; Paula B. Gomes; Carlos F. D. Gurgel; Alberto Lindner; Fernando L. Mantelatto; Alessandra K. G. Targino; Sergio R. Floeter (Marine Biology, 2022)

Quantitative comparison of the mean–return-time phase and the stochastic asymptotic phase for noisy oscillators - Alberto Pérez-Cervera; Benjamin Lindner; Peter J. Thomas (Biological Cybernetics, 2022)
Seminal work by A. Winfree and J. Guckenheimer showed that a deterministic phase variable can be defined either in terms of Poincaré sections or in terms of the asymptotic (long-time) behaviour of trajectories approaching a stable limit cycle. However, this equivalence between the deterministic notions of phase is broken in the presence of noise. Different notions of phase reduction for a stochastic oscillator can be defined either in terms of mean–return-time sections or as the argument of the slowest decaying complex eigenfunction of the Kolmogorov backwards operator. Although both notions of phase enjoy a solid theoretical foundation, their relationship remains unexplored. Here, we quantitatively compare both notions of stochastic phase. We derive an expression relating both notions of phase and use it to discuss differences (and similarities) between both definitions of stochastic phase for (i) a spiral sink motivated by stochastic models for electroencephalograms, (ii) noisy limit-cycle systems-neuroscience models, and (iii) a stochastic heteroclinic oscillator inspired by a simple motor-control system.

An updated phylogeny of the redlip blenny genus Ophioblennius - Naomi S. Lastrucci; Lucas T. Nunes; Alberto Lindner; Sergio R. Floeter (Journal of Fish Biology, 2018)
An updated molecular phylogeny of the blenny genus Ophioblennius , with a focus on two geographically disjunct morphotypes observed in Brazil, is presented. The analyses showed that specimens from the north‐eastern Brazilian coast are the endemic redlip blenny Ophioblennius trinitatis , but specimens from the southern Brazilian coast are conspecific to an undescribed east Atlantic Ocean (Gulf of Guinea) species, previously unknown in Brazil. Possible explanations for this geographical pattern include: natural larval dispersal and rafting across the Atlantic; an unknown ecological attribute that enabled this species to colonize southern Brazil; oil platforms as introduction vectors.

Contrasting patterns of connectivity among endemic and widespread fire coral species (Millepora spp.) in the tropical Southwestern Atlantic - Júlia N. de Souza; Flávia L. D. Nunes; Carla Zilberberg; Juan A. Sanchez; Alvaro E. Migotto; Bert W. Hoeksema; Xaymara M. Serrano; Andrew C. Baker; Alberto Lindner (Coral Reefs, 2017)

Overview of the order Zoantharia (Cnidaria: Anthozoa) in Brazil - Maria Eduarda Alves Santos; Marcelo Visentini Kitahara; Alberto Lindner; James Davis Reimer (Marine Biodiversity, 2016)

Genetic diversity of westerwold ryegrass landraces collected in Northwest Spain - Jose´ Alberto Oliveira; Ruth Lindner; Rezar Bregu; Alvaro García; Antonio Gonza´lez (Genetic Resources and Crop Evolution, 1997)